Acute effects of caffeinated chewing gum on volleyball performance in high-performance female players - Filip-Stachnik, A.; Kaszuba, M.; Dorozynski, B.; Komarek, Z.; Gawel, D.; Del Coso, J.; Klocek, T.; Spieszny, M.; Krzysztofik, M. (Journal of Human Kinetics, 2022)
To date, no investigation has studied the effect of acute intake of caffeinated chewing gum on volleyball performance. Therefore, the aim of this investigation was to establish the impact of caffeinated chewing gum ingestion on physical performance in female volleyball players. Twelve high-performance volleyball female athletes participated in a randomized, crossover, placebo-controlled, and double-blind experiment. Each athlete performed two identical experimental sessions after a) ingestion of ~6.4 mg/kg of caffeine via caffeinated chewing gum, b) ingestion of non-caffeinated chewing gum as a placebo. After the ingestion of gum, athletes performed a volleyball game, and performance was assessed by a notational analysis. Just before and after the game, jump performance during block and attack actions was evaluated. The number of points obtained and the number of errors committed during serve, reception, attacking, and blocking actions were unaffected by the ingestion of caffeinated chewing gum (p from 0.066 to 0.890). However, caffeinated chewing gum increased jump attack height in comparison to the placebo (pre-game 46.0 ± 7.2 vs. 47.2 ± 6.7 cm, p = 0.032; post-game 46.3 ± 7.6 vs. 47.5 ± 6.9 cm, p = 0.022, respectively). Caffeinated chewing gum did not modify block jump height (pre-game 32.7 ± 5.5 and 33.0 ± 4.3 cm, p = 0.829; post-game: 34.8 ± 6.1, 35.4 ± 6.1 cm, p = 0.993, respectively). The ingestion of ~6.4 mg/kg of caffeine via caffeinated chewing gum was effective for improving jump attack performance in women volleyball athletes. However, this effect was not translated into better volleyball performance during a game.